Killing the Canard: Saint Stephen’s Crown, Nixon, Budapest, and the Hungarian Lobby - Balogh, Máté Gergely (Hungarian Journal of English and American Studies, 2021)
With the question of the return of the Holy Crown in the focus, the essay describes how certain leaders of the Hungarian-American community attempted to influence American foreign policy towards Hungary during the détente period. Whereas certain members of the Nixon and Ford administrations, as well as the State Department, had already considered returning the Crown to the People’s Republic of Hungary, many of the émigré groups were strongly opposed to this action, and voiced their protest whenever speculations surfaced in the press. With the help of certain American and Hungarian-American politicians in Congress as well as in the Republican Party, the decision to return the Crown could be presented as potentially too risky politically and postponed during the Nixon and the Ford administrations. But with the election of President Carter, the Hungarian-American groups seem to have lost their leverage, and as soon as the political decision was made they could no longer prevent the return. (MGB)